Investigation of dielectric properties of LixNa₁₋xNbO₃ ceramics for x = 1 and x=4 - Bak, W.; Garbarz, B.; Smiga, W.; Kus, C. (Condensed Matter Physics, 1999)
The a.c. electrical response of LixNa₁₋xNbO₃ (LNN) solid solution in low frequency range (100 Hz–20 kHz) has been analysed as a function of temperature (300 K–750 K). A complex picture of the dependence of the studied properties on the chemical composition has been obtained. The data indicate the presence of relaxation and transport processes as well as their thermally activated character.